PENGARUH RASIO LIKUIDITAS TERHADAP PERKEMBANGAN KREDIT KUR PADA PT. BANK SUMUT CABANG GUNUNGSITOLI TAHUN 2021 - SYARIFA AINI; MARIA MAGDALENA BATE’E; YAKIN NIAT TELAUMBANUA (JURNAL ILMIAH SIMANTEK, 2022)
This journal discusses the effect of the Liquidity Ratio on the Development of KUR at PT. Bank Sumut Gunungsitoli Branch. The formulation of the research problem is, Does the Liquidity Ratio Affect the Development of KUR and How Much Does the Liquidity Ratio Influence the Development of KUR at PT. Bank Sumut Gunungsitoli Branch in 2021. The purpose of this study was to determine the influence of the Liquidity Ratio on the Development of KUR and to find out how much influence these two variables have. The type of research used is quantitative research with a descriptive approach. Furthermore, data management techniques and data analysis are carried out through Correlation Analysis, Simple Linear Regression Analysis, Coefficient of Determination, and Hypothesis Testing (t test). Judging from the results of the study, it shows that there is no influence of the Liquidity Ratio on the Development of KUR. The results of hypothesis testing with the t test show that the Liquidity Ratio partially has no influence on the Development of KUR. And the results of the correlation obtained a low relationship between the Liquidity Ratio to the development of KUR. The magnitude of the influence of the Liquidity Ratio on KUR development can be seen from the Determination Coefficient of 13.2% and the rest is influenced by other factors.